A Non-Muslim Teaching Islam: Pedagogical and Ethical Challenges. - Berkson, Mark (Teaching Theology & Religion, 2005)
This paper is a reflection on the two most significant challenges that I have faced teaching the introductory course in Islam. The first is the challenge of teaching Islam after September 11, 2001, the events of which gave rise to such pedagogical questions as how much and in what ways the course syllabus should change, and in particular how we should address issues such as extremism and terrorism. The second is the challenge of being a non-Muslim teaching Islam, which raises issues of authority (particularly when there are Muslim students in the classroom). The limitations and advantages of teaching a tradition as anoutsiderare explored, and strategies for compensating for the limitations are suggested. The final section of the essay explores the following question: When, if ever, can (or should) we as teachers move from explaining and analyzing the positions taken by members of a tradition to criticizing them?